Childhood Tuberculosis and its Relation with Nutrition: A five Year Retrospective Study - Chhetri, Uma; Mishra, Aparna; Jain, Kastur Chand; Bhandari, Keshav Raj (Journal of Lumbini Medical College, 2018)
Introduction: Tuberculosis is the sixth leading cause of mortality in Nepal. Childhood tuberculosis consisted 5.54% of newly registered 32,056 cases in 2016-17. Malnutrition is a predictor of tuberculosis and is associated with poorer outcomes. This study evaluates the clinico-epidemiologic profile of childhood tuberculosis and its relation to nutritional status. Methods: This was a retrospective review of 60 cases of tuberculosis admitted over a period of five years. Details regarding demographics, anthropometry, symptomatology and examination findings were retrieved. Diagnosis was categorized as pulmonary, extra-pulmonary and disseminated tuberculosis. Findings of various investigations were noted. Nutritional status of the patients was assessed using the WHO standard charts. Association of malnutrition and anemia with types and severity of tuberculosis was assessed. Results: A total of 60 patients were included in the study. Mean age was 7.9 years (SD = 4.6). The commonest presenting symptom was fever (83.3%) followed by decreased appetite (33.3%) and weight loss (26.7%). Cough was the predominant symptom in pulmonary tuberculosis (45%). Only eight cases were bacteriologically confirmed. Underweight, wasting and stunting were observed in 68.4%, 63.3% and 53.3% of cases respectively. Wasting was significantly associated with severe forms of tuberculosis (p = 0.03). Anemia was present in 89.5% of under five children (p = 0.02). Conclusion: Malnutrition often co-exists in a significant proportion of children with tuberculosis. Diagnosis in resource limited settings heavily relies on clinical suspicion and supporting investigations. Anemia is significantly associated with childhood TB, especially under five children. DOI: https://doi.org/10.22502/jlmc.v6i2.217